Plasma proteomic profiling of hospitalized patients co-infected with HIV and SARS-CoV-2 - Zhang, Xinyu; Yan, Xuan; Sun, Jinfeng; Shao, Yueming; Song, Wei; Qi, Tangkai; Wang, Zhenyan; Tang, Yang; Sun, Jianjun; Xun, Jingna; Song, Zichen; Xu, Shuibao; et al. (Frontiers in Immunology, 2025)
BackgroundThe interaction between human immunodeficiency virus (HIV) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections presents a critical challenge to immunopathogenesis. While HIV infection induces progressive CD4+ T cell depletion and chronic immune dysfunction, SARS-CoV-2 triggers complex host responses, ranging from localized antiviral defense to systemic hyperinflammation. We aimed to illustrate the plasma proteomic profiles of hospitalized patients coinfected with HIV and SARS-CoV-2.MethodsLiquid chromatography-tandem mass spectrometry was used to analyze the plasma protein profiles in three matched groups: (1) seven hospitalized patients with HIV and SARS-CoV-2 coinfection, (2) seven people living with HIV (PLWH) who tested negative for SARS-CoV-2, and (3) seven healthy controls. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses were performed on the differentially expressed proteins (DEPs).ResultsWe quantified 5,373 proteins across 21 samples and identified significant alterations in multiple proteins in people living with HIV (PLWH) with COVID-19 compared to both PLWH and healthy controls. These DEPs were associated with inflammatory responses, immune cell migration, degranulation, and, notably, the complement and coagulation cascades. In addition, we identified DEPs associated with SARS-CoV-2 infection, including viral receptors, proteases, transcription factors, and kinases.ConclusionsThe proteomic profile highlighted the disruption caused by COVID-19 in immunomodulation, thrombosis, and viral entry pathways in PLWH. Further validation of these signatures could improve risk stratification and tailored interventions for this vulnerable patient cohort.